Mental enlightenment scientific -methodological journal: The truth of life reflected in the story. - Soatova, nodira (FILOLOGIYA UFQLARI JURNALI, 2024)
This article is devoted to the issue tradition, conflict, conflict, skill. of the writer's ability to create the reality of life reflected in the stories of the 20th century writer Shuhrat. The article analyzes and interprets the author's use of philosophical-psychological image tools in the stories "Dakki", "Bahrinisa", "Quduq" by quoting excerpts from the stories. The article proves that the factor that fully ensured the life of famous stories is that the writer wrote them based on the events he saw and witnessed in life